Solar Plasma Structures and Solar Wind Plasma Turbulences in Relation with Geomagnetic Disturbances during Decline Phase of Solar Cycle 24 and Rising Phase of Solar Cycle 25 - Kumar, S.; Sharma, R.; Tripathi, O. P.; Verma, P. L. (Journal of Scientific Research, 2024)
We have studied the effect of solar structures and turbulences in solar wind plasma on the Earth's magnetosphere during the decline phase of solar cycle 24 and the rising phase of solar cycle 25. Most CMEs are geoeffective, cause geomagnetic storms, and are associated with C-class and M-class solar flares (S.F.s). It is also observed that these geomagnetic storms are associated with disturbances in solar wind plasma parameters. We have determined a large positive correlation with a correlation coefficient of 0.68, 0.58, 0.65, and 0.63 between the magnitude of the extensive geomagnetic storms and the peak value of IMF Btotal, the magnitude of IMF Btotal, the peak value of disturbances in the southward component of interplanetary magnetic fields (IMF Bz), and magnitude of disturbances in the southward component of interplanetary magnetic fields (IMF Bz). The correlation coefficient of 0.61 is higher between the magnitude of Dst and the magnitude of SWPT, as compared with the magnitude of flow pressure (0.39). From the present work, we have concluded that solar plasma structures and solar wind turbulences are mainly responsible for generating extensive geomagnetic storms.